Parenting Of Parents Work In Instilling Religious Attitudes And Respectful Attitudes In Adolescents - Fauziyah Fatmawati; Rifqi Aulia Erlangga (Profesional Muda Cendekia Publishing, 2021)
Parents, especially mothers are responsible for instilling the value of religious and social life in children, including adolescents through proper parenting. However, many parents choose to entrust the child completely to the school because it is busy with their work. This study aims to explain the parenting of working parents in instilling religious attitudes and respectful attitudes in adolescents, explain the factors that influence parenting, and explain the obstacles and solutions parents work in foster care. This study is a qualitative descriptive field study involving ten working parents. This research data is obtained through observation, interviews, and documentation. The results of this study found that the parenting used by sources is democratic parenting. Trust factors, comparison of parenting models, child gender, parental behavior, and character of children are factors that influence parenting in instilling religious attitudes and respectful attitudes in adolescents. In addition, there are obstacles in applying parenting, such as limited time together between parents and children because parents are busy working, child characters, mobile phones, child association, and social media. The solution in overcoming these obstacles is to be a good role model, make the best use of time to get to know the child's friendship environment, not only be a parent but can be a good friend and listener, and have to check the child’s phone.